CHONDRULE TEXTURES AND PRECURSOR GRAIN SIZE: AN EXPERIMENTAL STUDY - Hewins R.H.; Fox G.E. (My University, 2004)
Chondrule formation appears to have been a major event in the early solar system, but chondrule properties do not allow us to distinguish between several possible formation mechanisms. The physical nature of the precursors, especially grain size, must affect the textures of the chondrules they yield when heated. We melted precursors of different grain sizes, including extremely fine-grained crystalline aggregates analogous to nebular condensates, to see whether objects resembling most natural chondrules can be crystallized. With one-minute heating and moderate cooling rates, the grain size of the charges depends directly on the grain size of the starting material, for temperatures up to very close to the liquidus temperature. A single rapid heating of condensate-like material thus produces very fine-grained chondrules, like dark-zoned chondrules, for a very wide range of peak temperatures. It is incapable of generating the observed textural distribution of chondrules, which are predominantly porphyritic. The simplest model for chondrules, a single heating of unmodified condensate material, therefore appears unrealistic. Coarse-grained chondrules might be formed from fine-grained precursors by extended heating with evaporation leading to coarsening, or by multiple reheating events, with higher temperatures in subsequent events. Otherwise an origin from annealed condensates, planetary rocks, or by condensation of liquid and crystals is required.
Keywords: Chondrule